The Efficacy of Endoscopic Papillary Balloon Dilation for Patients with Acute Biliary Pancreatitis. (9th April 2015) - Sun, Wei-Chih; Chan, Hoi-Hung; Lai, Kwok-Hung; Tsai, Tzung-Jiun; Lin, Huey-Shyan; Lin, Kung-Hung; Wang, Kai-Ming; Kao, Sung-Shuo; Chiang, Po-Hung; Cheng, Jin-Shiung; Hsu, Ping-I; Tsai, Wei-Lun; et al.
Abstract : Background . No study investigated the efficacy and safety of endoscopic papillary balloon dilation (EPBD) for the treatment of acute biliary pancreatitis (ABP). Method . We retrospectively reviewed the effects of EPBD on patients with ABP from February 2003 to December 2012. The general data, findings of image studies, details of the procedure, and outcomes after EPBD were analyzed. Result . Total 183 patients (male/female: 110/73) were enrolled. The mean age was 65.9 years. Among them, 155 patients had mild pancreatitis. The meantime from admission to EPBD was 3.3 days. Cholangiogram revealed filling defects inside the common bile duct (CBD) in 149 patients. The mean dilating balloon size was 10.5 mm and mean duration of the dilating procedure was 4.3 minutes. Overall, 124 patients had gross stones retrieved from CBD. Four (2.2%) adverse events and 2 (1.1%) intraprocedure bleeding incidents but no procedure-related mortality were noted. Bilirubin and amylase levels significantly decreased after EPBD. On average, patients resumed oral intake within 1.4 days. The clinical parameters and outcomes were similar in patients with different severity of pancreatitis. Conclusion . EPBD can be effective and safe for the treatment of ABP, even in patients presenting with severe disease.